Research Methodology - Pruzan Peter (Springer, 2016)
This book is an in-depth guide to effective scientific research. Ranging from the philosophical to the practical, it explains at the outset what science can - and can't - achieve, and discusses its relationship to mathematics and laws. Introduction, Science, Hypotheses and Theories and Laws, Scientific Statements: Their Justification and Acceptance, Measurement, Experimentation, Scientific Method and the Design of Research, Uncertainty and Probability and Statistics in Research, Research, Ethics and Responsibility in Scientific Research, References, Index.